Pioneering Agriculture-Based Edutourism in Wonosari Village, Gondangrejo Subdistrict, Karanganyar Regency - Sumani Sumani; Haikal Rafi Wardhana; Febiana Suci Imawati; Muhammad Rosyid Fauzi; Raden Ajeng Alma; Sandrina Sari; Zainal Isa Abidin; Aldarisma Nur Aini; Fara Cahyawati (Universitas Sebelas Maret, 2024)
Edutourism combines education and tourism, means traveling and learning simultaneously. Most of the people in Wonosari Village live from farming, have opportunity to develop agriculture-based edutourism, which can be realized as a tourist garden with various agricultural plants. The development of edutourism in Wonosari Village aims to educate the surrounding community, especially school-aged children, by introducing various food source plants. It’s also essential to increase local village communities' awareness of the potential of their environment, which can be used as a tourist attraction and an object for agriculture learning. The pioneering activities for the creation of an edutourism park were carried out in several stages, starting with the socialization of the edutourism park, surveying the location for the creation of the edutourism park, planting of crops including corn, chilies, long beans, and eggplant. The next stage is assistance in making organic fertilizers and pesticides, making infographics regarding edutourism gardens, including plant taxonomy, plant water needs, fertilizer needs, cultivation stages, and explanations regarding pests of several types of plants in Wonosari Village. In the final stage, we invited MI students to visit the pioneering educational tourism park. The activity results were the realization of a pilot agricultural plantation with corn, chili, long bean, and eggplant plants and infographics, located in Munggur Hamlet, Wonosari Village, Gondangrejo District, Karanganyar Regency. It can be concluded that Wonosari Village has excellent potential for developing agriculture-based edutourism, which can support the advancement of the welfare of village residents and increase tourists' knowledge about agriculture.